The Network Approach in Portfolio Management - Barczak, Beata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The increased complexity of projects and the high complexity of managing numerous projects make project portfolio management an area in which network issues still offer inspiring research potential. The theory of organisational networks creates wide possibilities in project portfolio management. The article discusses the application of a network approach in the analysis of project portfolios and indicates new directions in research on project portfolios resulting from the adoption of the network perspective. The article presents three main issues: the concept of the organisational network and its reference to project portfolio management, an interpretation of concepts related to project portfolio management and the network approach to project portfolios. The application of network theory to research on project portfolios, in particular the use of the network analysis method (SNA, or Social Network Analysis), makes it possible to formulate and describe the characteristics of project networks.